Anterior Tooth Rehabilitation With Frozen Homogenous Bone Graft and Immediately Loaded Titanium Implant Using Computer-Guided Surgery - Margonar, Rogerio; Queiroz, Thallita Pereira; Luvizuto, Eloa Rodrigues [UNESP]; Santos, Pamela L. [UNESP]; Wady, Amanda Fucci [UNESP]; Paleari, Andre Gustavo [UNESP] (Lippincott Williams & Wilkins, 2012)
Computed tomographic scanning is a precise, noinvasive surveying technique that enables the professionals to improve the precision of implant placement by building a prototype that allows the confection of surgical guides. The authors present a clinical case of anterior tooth rehabilitation with frozen homogenous bone graft and immediately loaded titanium implant using computer-guided surgery. A multislice computed tomography was realized, and a prototype was built. All the procedures were previously realized in the prototype before started in the patient. This technique allows a better surgical planning, makes the procedures more accurate, and reduces surgery time.
Keywords: Computed tomography scan; guided surgery; mandible; implants; prosthesis